Mitral and aortic regurgitation in Rheumatic heart diseases (University Heart Journal, 2026)
Rheumatic heart disease is a systemic immune process that is sequelae to a beta-hemolytic streptococcal infection of the pharynx. It is most common in developing countries. It is responsible for 250,000 deaths in young people worldwide each year. Over 15 million people have evidence of rheumatic heart disease. The long-term damage to cardiac valves caused by ARF, which can result from a single severe episode or from multiple recurrent episodes of the illness, is known as rheumatic heart disease (RHD) and is a notable cause of morbidity and mortality in resource-poor settings around the world. Although our understanding of disease pathogenesis has advanced in recent years, this has not led to dramatic improvements in diagnostic approaches, which are still reliant on clinical features using the Jones Criteria, or treatment practices. Indeed, penicillin has been the mainstay of treatment for decades and there is no other treatment that has been proven to alter the likelihood or the severity of RHD after an episode of ARF. Recent advances — including the use of echocardiographic diagnosis in those with ARF and in screening for early detection of RHD, progress in developing group A streptococcal vaccines and an increased focus on the lived experience of those with RHD and the need to improve quality of life — give cause for optimism that progress will be made in coming years against this neglected disease that affects populations around the world, but is a particular issue for those living in poverty.The acute illness can be severe, with disabling pain from arthritis, breathlessness and oedema from heart failure, high fevers and choreiform movements that impair activities of daily living. ARF is usually best managed in hospital, often for a 2–3 week period, by which time the diagnosis is confirmed and the symptoms are treated. Although most of the clinical features of ARF will resolve during this short hospital stay, the cardiac valvular damage might persist. This chronic valvular damage is known as rheumatic heart disease (RHD) and is the major cause of morbidity and mortality from ARF. ARF can recur as a result of subsequent GAS infections and each recurrence can worsen RHD. Thus, the priority in disease management is to prevent ARF recurrences using long-term penicillin treatment, which is known as secondary prophylaxis. The persistent damage to heart valves resulting in mitral and/or aortic regurgitation, or in long-standing cases stenosis, that remains as a result of acute rheumatic fever with rheumatic carditis. Complications of rheumatic heart disease include heart failure, embolic stroke, endocarditis and atrial fibrillation.University Heart Journal 2026; 22(1): 44-47